2018
DOI: 10.1108/gkmc-04-2018-0033
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Sokoine University of Agriculture Institutional Repository among academic staff at the College of Veterinary Medicine and Biomedical Science in Tanzania

Abstract: Purpose -This study aims to investigate the use of Sokoine University of Agriculture Institutional Repository (SUAIR) among academic staff at the College of Veterinary Medicine and Biomedical Science (CVBMS). Specifically, the study looked at awareness of, attitude, self-archiving and challenges the academic staff face when using SUAIR.Design/methodology/approach -The study used survey method. The data were collected using selfadministered questionnaire with the results analysed using descriptive statistics.Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, recent studies carried out at Annamalai University, Tamil Nadu, India, and in Nigeria report that despite efforts by universities to establish OAIRs, there were some academic staff who were not aware of the existence of OAIRs in their universities (Aghwotu and Ebiere, 2016; Dhanavandan and Tamizhchelvan, 2013). Despite the fact that some academic staff are aware of the presences of OAIRs in their universities, the amount of content deposited in OAIRs is low, especially in Tanzania (Chilimo, 2016; Mnzava and Chirwa, 2018; Samzugi, 2017). Therefore, this study was conducted to find out the level of awareness of the presence of OAIRs in universities and the process of self-archiving locally produced content in university OAIRs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies carried out at Annamalai University, Tamil Nadu, India, and in Nigeria report that despite efforts by universities to establish OAIRs, there were some academic staff who were not aware of the existence of OAIRs in their universities (Aghwotu and Ebiere, 2016; Dhanavandan and Tamizhchelvan, 2013). Despite the fact that some academic staff are aware of the presences of OAIRs in their universities, the amount of content deposited in OAIRs is low, especially in Tanzania (Chilimo, 2016; Mnzava and Chirwa, 2018; Samzugi, 2017). Therefore, this study was conducted to find out the level of awareness of the presence of OAIRs in universities and the process of self-archiving locally produced content in university OAIRs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most academic staff do not engage in self-archiving or give their academic work to be deposited in university OAIRs (Aghwotu and Ebiere, 2016; Dutta and Paul, 2014; Ezema and Okafor, 2015; Halder and Chandra, 2012; Omeluzor, 2014). Other studies have also found that there are several challenges with regard to depositing or self-archiving locally produced content in OAIRs, such as lack of awareness of the process, time limitations, lack of technical skills, an unstable network and electricity problems (Halder and Chandra, 2012; Mnzava and Chirwa, 2018; Omeluzor, 2014). Different studies have been carried out in Tanzania (Chilimo, 2016; Mnzava and Chirwa, 2018; Samzugi, 2017) but it is still not clear how academic staff engage in self-archiving, which drove the researchers to embark on this study.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies related to IRs in Tanzania have not addressed the impact of IRs. Nunda and Elia (2018) Samzugi (2017) and Muneja (2016) focused on the adoption and implementation of IRs; Mbughuni (2022), Mnzava and Chirwa (2018) studied the contents and usage of IRs; Kakai et al (2018), Kodua-Ntim and Fombad (2020) and Muneja and Ndenje-Sichalwe (2017)assessed the open access and copyright issues. Similar studies assessing the IR impact have been conducted in other countries; for instance, Ndhlovu (2021)evaluated the impact of IR contents in Zimbabwe, and Wheel et al (2022) assessed the impact of institutional repositories in the USA, Austria, Columbia, and Mexico.…”
Section: Introductionmentioning
confidence: 99%